S78 Dupilumab reduces risk of severe exacerbations and improves FEV1 regardless of baseline disease severity in patients with uncontrolled, moderate-to-severe asthma: data from the phase 3 LIBERTY ASTHMA QUEST study. (December 2018) - Pavord, I; Papi, A; Wenzel, S; Park, HS; Rice, M; Staudinger, H; Maroni, J; Rowe, P; Rout, R; Amin, N; Akinlade, B; Graham, NMH; et al.
Abstract : Introduction and objectives: Dupilumab, a fully human anti-interleukin (IL)−4α monoclonal antibody that inhibits IL-4 and IL-13, key drivers of Type 2 inflammation, is approved for treatment of adults with inadequately controlled moderate-to-severe atopic dermatitis. In a double-blind, placebo-controlled phase 3 study (NCT02414854 ), patients with asthma aged ≥12 years, without a minimum baseline eosinophil requirement and uncontrolled with medium-to-high-dose inhaled corticosteroids (ICS) plus up to two additional controllers, received add-on dupilumab 200 mg or 300 mg or matched placebo every 2 weeks (q2w) for 52 weeks. In the overall intent-to-treat population, both dupilumab doses significantly reduced annualized severe exacerbation rates during the 52 week treatment period, improved pre-bronchodilator forced expiratory volume in 1 s (FEV1 ), improved quality of life measures, and were generally well tolerated. This pre-specified analysis assessed the efficacy of dupilumab by disease severity determined by baseline ICS dose (high/medium). Methods: Annualized severe exacerbation rates during the 52 week treatment period and change from baseline in pre-bronchodilator FEV1 at Week 12 were analyzed by baseline ICS dose (high/medium) subgroup. These parameters were further analyzed by subgroups defined by baseline levels of eosinophils (≥300 cells/µL) and fractional exhaled nitric oxide levels (FeNO;≥25 ppb). Results: Both dupilumab q2w doses significantly reduced annualized severe exacerbation rates over the 52–week treatment period (p<0.01) compared to placebo and improved pre-bronchodilator FEV1 at Week 12 (p<0.01) regardless of baseline ICS dose (figure 1). Overall, reduction in exacerbation rate and improvement in FEV1 appeared similar between high- and medium-dose ICS subgroups with increased efficacy in subgroups with baseline eosinophil levels of ≥300 cells/µL (both p<0.01) or baseline FeNO level of ≥25 ppb (both p<0.01). The most frequent adverse event occurring at higher frequency in the dupilumab groups vs placebo was injection-site reaction (15%/18% vs 5%/10%, respectively). Conclusions: Add-on dupilumab significantly reduced the rate of severe exacerbations, and improved FEV1 in patients with moderate or severe asthma (as assessed by medium or high ICS dose at baseline). Dupilumab demonstrated increased efficacy in patients with higher levels of Type 2 inflammation, as defined by elevated baseline eosinophil counts and FeNO levels. Dupilumab was generally well tolerated. Please refer to page A265 for declarations of interest related to this abstract.